Development of Android Applications SAJ (Sinau Aksara Jawa) as Javanese Script Learning Media Using the Addie Model - Sugito Sugito; I Nyoman Sudana Degeng; Ibut Priono Leksono (EDUCATIO: Journal of Education, 2023)
This study aims to develop learning media based on Android for Javanese language lessons on Javanese script material. With this learning media, students are expected to be able to learn more effectively and efficiently because they can learn anytime and anywhere. The model used in this development is the ADDIE development model which has 5 steps, namely: (1) Analysis, (2) Design, (3) Development, (4) implementation, (5) Evaluation. The results of this development research are in the form of an android-based Javanese script learning application called SAJ (Sinau Javanese Script). In the development process to get a product that is by the objectives, it is continuously validated by content experts, design experts, media experts, and student responses. The results of the validation by content experts obtained a total score of 67 percentage 94% very feasible category, from design experts obtained a total score of 49 with a percentage of 94% very feasible category, while media experts obtained a score of 67 percentage 93% very feasible category. The test was carried out twice, the first was a small group with a percentage of 95.7% in the very feasible category, the field test obtained a percentage of 96.9% in the very feasible category. Thus, students can use the product developed as a medium for learning Javanese script.